SURG-06. LASER ABLATION FOR BRAIN METASTASES: SAFETY AND PRELIMINARY OUTCOMES FROM THE LASER ABLATION OF ABNORMAL NEUROLOGICAL TISSUE USING ROBOTIC NEUROBLATE SYSTEM (LAANTERN) REGISTRY. (5th November 2018) - Kamath, Ashwin; Tatter, Stephen; Fecci, Peter; Chen, Clark; Chiang, Veronica; Rao, Ganesh; Mohammadi, Alireza; Judy, Kevin; Field, Melvin; Neimat, Joseph; Leuthardt, Eric; Kim, Albert
Abstract: INTRODUCTION: Laser Interstitial Thermal Therapy (LITT) is a novel technology that offers a minimally invasive option for brain metastases. The current understanding of LITT in this context is limited by small sample size or to single center experiences. Laser Ablation of Abnormal Neurological Tissue using Robotic NeuroBlate System (LAANTERN) is a registry designed to address these limitations. We present the preliminary experience with regard to safety, procedural data, and preliminary outcomes of LITT for brain metastases. METHODS: LAANTERN is an ongoing registry that collects data on patients treated with the NeuroBlate® system. Data presented here include procedural data, complications, and survival. RESULTS: Fifty-one brain metastases in 50 patients (33 male, 17 female) were treated with LITT. Mean age was 58.3 ± 13.4 years (range 25–80 years). 48 patients (96%) had prior treatment(s) to the target lesion, including surgery, chemotherapy, and radiation. 49 lesions (96.1%) were treated with a single trajectory, and 2 (3.9%) were treated with two trajectories. Location of lesions were frontal lobe (26, 51%), followed by parietal (10, 19.6%) and temporal (9, 17.6%) lobes. Average lesion volume was 2.9 ± 3.2cm3. Volumetric data was available for 48 patients; of these, 40 (83%) had 91–100% ablation coverage based on physician determination; eight (16.7%) had 51–90% ablation coverage. The 91–100% group had a death rate of 18.9%; the 51–90% group had a death rate of 37.5% (p=0.35). Adverse events occurred in 5 (10%) patients within 30 days of procedure. There were no mortalities in this timeframe. Median follow up was 6 months; median overall survival has not yet been reached. Kaplan-Meier survival estimates at 1, 6, and 12 months were 90%, 76%, and 71%, respectively. CONCLUSION: Preliminary results from the LAANTERN registry demonstrate an acceptable safety profile, procedural efficacy, and satisfactory outcomes of LITT in carefully selected patients with brain metastases.